The Formation of Bilateral FTA in Political-Economic Perspective: Comparing the US and the Japanese Model of FTA - Siti Daulah Khoiriati (Journal of World Trade Studies, 2013)
The formation of bilateral Free Trade Agreement (FTA) has proliferated in various regions since the United States (US) initiated the formation of NAFTA in 1992. What was striking from the phenomenon was that many FTAs were formed between developed and developing countries not only regionally but also cross-regionally. In fact, only a fraction of initiated FTAs successfully delivered the expectations of the parties involved. Conversely, it tended to yield unequal economic benefit to the parties. This has raised the question of: why states rush to jump on FTA bandwagon? Many analysts argued that states form bilateral FTA for the sake of reputation without considering much the consequences derived from such arrangements. This article examines the motives, interests, and preferences of states in forming FTA using political-economic approach, to clarify the determinants of FTA formation. Presenting the case of the United States (US) and Japan—two influential advanced economy states in international trade— this article took the US FTA model and the Japanese FTA model into considerations, provided analytical explanations on the political-economic reasons behind the devel¬oped countries' initiative to form FTA, and its implications for developing countries.